THE IMPACT OF SENSORY MARKETING ON CONSUMER’S BUYING BEHAVIOR OF COFFEE SHOPS IN MANADO - Stephanie Ludya Natalia; David P. E. Saerang; Shinta J. C. Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Customer buying behavior have close relation with sensory marketing because it has connection with the customers itself, mainly about how the perception of the customers toward certain marketing campaign. The problem related with the phenomenon of Sensory Marketing now is about how to incorporate this type of marketing to MSMEs which include local artisan coffee shops in Manado. This research is expected to add more knowledge about the application of sensory marketing to achieve its best values. Using Quantitative Approach, this research derived and examined the model through multiple linear regression model in a sample of 100 respondents which are customers of local coffee shops in Manado. The suggestion for the coffee shops is to improve the quality of atmosphere within the shop, adding more decorations, air conditioner and other will enhance the atmosphere even more. Atmosphere of the shop is crucial because it is the place where customers can enjoy the products or do other activities, therefore it is essential for the shop to do innovation regarding the atmosphere of coffee shops.   Keywords: sensory marketing, consumer’s buying behavior, human senses